Implementation of Expert System for Detection Periodontitis Disease Using Fuzzy Logic - Hardi, Sri Melvani; Siagian, Deliyana; Efendi, Syahril (ZERO: Jurnal Sains, Matematika dan Terapan, 2020)
The wellbeing area is one region that requires innovation in technology. Wellbeing is for sure a costly thing for people. In this manner it takes individual affectability to care for it. One of the solid organs that people frequently disregard is teeth and mouth. Periodontitis is a dental and oral illness that is frequently grumbled of by numerous individuals. In any case, as of recently, periodontitis has not been a critical worry of Indonesian individuals. It is important to give data and comprehension about periodontitis side effects to dynamic smokers by making an expert system. A system is expected to distinguish the underlying indications and straightforwardly beat these side effects. The expert system is a part of Computer Science that fills in as a spot to move information from specialists so computers can have the aptitude to tackle issues utilizing these specialists' information. The technique utilized in this examination is the Fuzzy Logic strategy. This present investigation's eventual outcomes are analytic outcomes from the fluffy rationale technique, where the exactness of the Fuzzy Logic strategy is 93.33%.